2015
DOI: 10.4049/jimmunol.1500651
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Resident NK Cells Mediate Ischemic Kidney Injury and Are Not Depleted by Anti–Asialo-GM1 Antibody

Abstract: NK cells are innate lymphoid cells important for immune surveillance, identifying and responding to stress, infection, and/or transformation. While conventional NK (cNK) cells circulate systemically, many NK cells reside in tissues where they appear to be poised to locally regulate tissue function. Here we tested the contribution of tissue-resident NK (trNK) cells to tissue homeostasis by studying ischemic injury in the mouse kidney. Parabiosis experiments demonstrate that the kidney contains a significant fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 78 publications
2
104
1
Order By: Relevance
“…NK cells have previously been shown to be important for RIR injury (911). NK cells produce toxic molecules such as perforin and granzymes that induce cell death (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NK cells have previously been shown to be important for RIR injury (911). NK cells produce toxic molecules such as perforin and granzymes that induce cell death (12).…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune cells such as natural killer (NK) cells, neutrophils, and macrophages become activated and migrate to the tissue, which causes further cellular injury of the TECs through the release of cytokines and reactive oxygen species (7, 8). Of the innate immune cells, NK cells are cytotoxic lymphocytes which play a critical role in RIR injury (911). These cells contain perforin and granzymes, and upon release in proximity to target cells, perforin forms pores in the cell membrane through which granzymes can enter, causing apoptosis or osmotic cell lysis (12).…”
Section: Introductionmentioning
confidence: 99%
“…Thymic NK cells represent another population that develops from unique precursors, and are Ly49 low CD11b low and CD127 + CD69 high , in contrast to cNK cells (4, 5). A unique population of trNK cells has also recently been discovered in the kidneys (6). The current understanding is that cNK cells, together with liver and skin trNK (ILC1), uterine NK cells, thymic NK cells, and kidney trNK cells, account for multiple distinct NK cell lineages (3, 7).…”
Section: Introductionmentioning
confidence: 99%
“…One study found that antiasialo GM1 does not deplete tissue-resident NK cells in the kidney. 53 But within that same article, the authors have shown that uterine tissue-resident NK cells seem to be an exception because they were uniformly expressing high levels of asialo GM1 that was similar to circulating NK cells in some strains. 53 Currently, the only way of temporarily depleting or reducing NK cells in the rat is administering antibodies or the antiserum anti-asialo GM1.…”
Section: Discussionmentioning
confidence: 99%